2011
DOI: 10.1371/journal.pone.0028423
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mir-21 and Mir-143 in Cervical Specimens Ranging from Histologically Normal through to Invasive Cervical Cancer

Abstract: BackgroundMicroRNA expression is severely disrupted in carcinogenesis, however limited evidence is available validating results from cell-line models in human clinical cancer specimens. MicroRNA-21 (mir-21) and microRNA-143 (mir-143) have previously been identified as significantly deregulated in a range of cancers including cervical cancer. Our goal was to investigate the expression patterns of several well-studied microRNA species in cervical samples and compare the results to cell line samples.Methodology/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 52 publications
8
59
0
3
Order By: Relevance
“…Local and systemic metastasis is a major cause leading to a dismal prognosis of CC. Increasing evidence has confirmed miRNAs as key regulators in the metastasis of various types of cancer, including CC (27). In the present study, we found that miR-1297 was significantly downregulated in CC tissues compared with the corresponding non-cancerous tissues.…”
Section: Discussionsupporting
confidence: 71%
“…Local and systemic metastasis is a major cause leading to a dismal prognosis of CC. Increasing evidence has confirmed miRNAs as key regulators in the metastasis of various types of cancer, including CC (27). In the present study, we found that miR-1297 was significantly downregulated in CC tissues compared with the corresponding non-cancerous tissues.…”
Section: Discussionsupporting
confidence: 71%
“…Nuovo et al 2010 (5) have shown a strong inverse correlation between this microRNA and HPV DNA in productive infection in cervical cancer. Other microRNAs observed in our study, such as microRNA-21, have also been identified as significantly deregulated in a range of cancers, including cervical cancer (26). miR-16 seems to be important within HPV pathogenesis in head and neck squamous cell carcinomas (27).…”
Section: Discussionsupporting
confidence: 61%
“…A number of studies have identified miRNA-143 as a tumor suppressor gene lost expression significantly in several cancer types, including breast and cervical cancers [10][11][12][13], which is consistent with our results on the expression of miRNA-143 in cervical cancer tissues. miRNA-143 was expressed at significantly lower levels when compared to the normal control tissues.…”
Section: Discussionsupporting
confidence: 92%